2017
DOI: 10.1002/eco.1888
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the key drivers of riparian woodland successional pathways across three European river reaches

Abstract: International audienceClimate change and river regulation are negatively impacting riparian vegetation. To evaluate these impacts, process‐based models are preferred over data‐driven approaches. However, they require extensive knowledge about ecohydrological processes. To facilitate the implementation of such process‐based models, the key drivers of riparian woodland successional pathways across three river reaches, in Austria, Portugal, and Spain, were explored, employing two complementary approaches. The pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 118 publications
1
8
0
1
Order By: Relevance
“…Other converging pathways were identified earlier, within the FBS model (Corenblit et al, ), as well as by other authors, without referring to the FBS model (Bendix & Hupp, ; Egger et al, ). This stresses the importance of identifying specific physical (hydrogeomorphological) and/or biological drivers for the successional pathway or trajectory considered (Muñoz‐Mas et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Other converging pathways were identified earlier, within the FBS model (Corenblit et al, ), as well as by other authors, without referring to the FBS model (Bendix & Hupp, ; Egger et al, ). This stresses the importance of identifying specific physical (hydrogeomorphological) and/or biological drivers for the successional pathway or trajectory considered (Muñoz‐Mas et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in wetland communities, this disturbance does not necessarily kill the seeds, but can induce a spatial storage effect that favorably influences the species richness of seeds, seed abundance, and germination ability at the community level when compared to an undisturbed landscape (Devictor et al, 2007). Hydrological gradients also interact with interspecific interactions and competition to determine undisturbed community assemblages (Muñoz-Mas et al, 2017) and have been found to create differences in seed density and species diversity (Bekker et al, 2000). It is, therefore, necessary to consider the relationship between hydrological gradients and anthropogenic disturbance, such as plowing, to understand and predict the plant community that emerges and establish, which can be especially useful in the ecological restoration of previously disturbed sites.…”
Section: Introductionmentioning
confidence: 99%
“…At this fourth stage, the biogeomorphological entities have reached their stage of exosystemic maturity as functional units with many interacting species (e.g., bacteria, mycorrhiza, insects, invertebrates, plants) capable of supporting the nutritional requirements and sexual reproduction of the large mature trees. Only exceptional floods and lateral erosion of the banks or anthropogenic activities are capable to cause the complete destruction of such stabilized and resistant biogeomorphological entities (Jourdain et al, 2017;Martínez-Fernández et al, 2017;Muñoz-Mas et al, 2017). We suggest that the vegetated islands, banks and floodplains are potentially the result of a positive niche construction (Odling-Smee et al, 2003) by pioneer engineer trees.…”
Section: Abridged English Versionmentioning
confidence: 81%
“…Les entités biogéomorphologiques ont atteint leur stade écosystémique de maturité en tant qu'unité fonctionnelle de l'écosystème riverain comportant de nombreuses espèces en interaction (e.g., bactéries, mycorhizes, invertébrées, insectes, plantes) capables de soutenir les besoins nutritifs et la reproduction sexuée des grands arbres matures. Désormais, seules les crues exceptionnelles, l'érosion latérale des chenaux pendant des débits à pleins bords, ou les activités anthropiques sont en mesure de causer leur destruction complète (Dufour et Piégay, 2010 ;Jourdain et al, 2017 ;Martínez-Fernández et al, 2017 ;Muñoz-Mas et al, 2017). La durée de la phase écologique dépend ainsi de la fréquence et de la magnitude des crues destructrices, mais aussi du degré de mobilité latérale du ou des chenaux qui peut causer, par sapement latéral, la destruction de ces entités biogéomorphologiques (Jourdain et al, 2017).…”
Section: Fig 7 -Model Of Black Poplar Root Growth After Floodsunclassified